Layered Metal Nanoparticle Structures on Electrodes for Sensing, Switchable Controlled Uptake/Release, and Photo‐electrochemical Applications. Issue 1 (30th October 2015) - Tel‐Vered, Ran; Kahn, Jason S.; Willner, Itamar
Abstract : Layered metal nanoparticle (NP) assemblies provide highly porous and conductive composites of unique electrical and optical (plasmonic) properties. Two methods to construct layered metal NP matrices are described, and these include the layer‐by‐layer deposition of NPs, or the electropolymerization of monolayer‐functionalized NPs, specifically thioaniline‐modified metal NPs. The layered NP composites are used as sensing matrices through the use of electrochemistry or surface plasmon resonance (SPR) as transduction signals. The crosslinking of the metal NP composites with molecular receptors, or the imprinting of molecular recognition sites into the electropolymerized NP matrices lead to selective and chiroselective sensing interfaces. Furthermore, the electrosynthesis of redox‐active, imprinted, bis‐aniline bridged Au NP composites yields electrochemically triggered "sponges" for the switchable uptake and release of electron‐acceptor substrates, and results in conductive surfaces of electrochemically controlled wettability. Also, photosensitizer‐relay‐crosslinked Au NP composites, or electrochemically polymerized layered semiconductor quantum dot/metal NP matrices on electrodes, are demonstrated as functional nanostructures for photoelectrochemical applications. Abstract : Layered metal nanoparticles are assembled on surfaces or thin, metal film‐coated surfaces by supramolecular interactions or by electrochemical crosslinking and the generation of covalent bridging units. The resulting composite‐modified electrodes act as sensing devices, as stimuli‐responsive "sponges" for the controlled uptake/release of different materials, and as photoelectrochemical electrodes.